Developing Soft Skills using "Literature Circles" - Latiff Azmi, Mohd Nazri (2013)
This study investigates the impact of the implementation of ‘Literature Circles’ in an Active Learning classroom in relations to developing soft skills among university students. The use of Literature Circles is a well-known strategy in teaching the students to be more creative, independent and think out of the box. A group of thirty three students was involved in this seven weeks teaching and learning session. Towards the end of the period of implementation, the researcher found a gradually positive impact in developing soft skills and also linguistic skills. This action research has given a huge impact not only to the language teaching and learning session but also in molding a better curriculum design for a betterment of the education system.